Effect of SARS-CoV-2 infection on liver function in patients with hepatitis B - Tong Sun; Hongbo Chi; Jing Wang; Yufen Zheng; Hongguo Zhu; Jingxian Zhao; Kai Zhou; Mengyuan Chen; Donglian Wang; Tao-Hsin Tung; Jiaqin Xu; Bo Shen (BMC Infectious Diseases)
Abstract Objective To investigate the impact of SARS-CoV-2 infection on liver function and prognosis in patients with HBV infection. Methods A total of 154 HBV-positive patients (HBV ( +) group) and 154 HBV-negative patients (HBV (-) group) diagnosed with COVID-19 at Taizhou Hospital between December 10, 2022, and January 31, 2023, were included in this study. Clinical characteristics, treatment, and laboratory findings were collected from patients at three time points: before (T1), during (T2), and at the time of discharge (T3) from SARS-CoV-2 infection. Results Compared to the HBV (-) group, the HBV ( +) group had a longer hospital stay (15 (9–22) days vs. 9 (5–16) days). Longitudinal comparisons of laboratory indicators from T1 to T3 showed a continuous decline in TP and ALB levels and a continuous increase in PT and TT levels in the HBV ( +) group. BUN levels increased during T2 and decreased thereafter. These differences were considered statistically significant (P < 0.05). Notably, the HBV ( +) group had a higher proportion of indicators elevated > 3 ULN from T1 to T2, including ALT (1.95%/5.19%), AST (3.25%/12.99%), ALP (1.95%/3.25%), GGT (4.55%/9.09%), TBIL (6.49%/9.09%), and DBIL (18.18%/22.73%). In the HBV (-) group, the elevations were mainly concentrated within 1–2 ULN, including AST (12.99%/22.08%), DBIL (10.39%/21.43%), BUN (12.99%/22.08%), CREA (20.13%/29.22%), and PLT (7.79%/14.94%). Furthermore, the incidence of liver injury from T1 to T3 was higher in the HBV ( +) group compared to the HBV (-) group (15.7% (20/127) vs. 7.2% (11/152), P < 0.05). Multivariate analysis showed that liver cirrhosis (HR = 4.847, 95% CI: 1.224–19.20, P = 0.025) and liver cancer (HR = 8.333, 95% CI: 2.156–32.209, P = 0.002) were independent risk factors for liver injury in the presence of SARS-CoV-2 infection. Conclusion SARS-CoV-2 infection has a higher proportion of liver injury in HBV-infected patients, affecting hepatic protein synthesis function. Those with cirrhosis and hepatocellular carcinoma are at higher risk of severe liver injury.